Oscar — 2022: Hamaguchi Ryūsuke - E. L. Katasonova (Ежегодник Япония, 2022)
The article is devoted to the work of the famous Japanese film director Hamaguchi Ryūsuke — a representative of the new generation of Japanese cinematographers. He is the winner of many prestigious awards of the international film festivals in Locarno, Cannes, etc. His film Drive My Car received the prize of the American Film Academy, Oscar — 2022, as the best foreign film. The film is unusual and interesting in many of its features, which are described in detail in this paper. But, first of all, the author draws attention to the fact that the plot of this picture is based on the eponymous story by the popular Japanese novelist Murakami Haruki. At the same time, the director borrowed a lot from the play “Uncle Vanya”, written by Russian classic A. P. Chekhov, whose influence is quite evident in all the director’s recent works. Another key figure who determined the main vector of creativity of Hamaguchi is Andrei Tarkovsky. The Japanese director owes his acquaintance with Tarkovsky’s films to his teacher — a master of modern Japanese cinema Kurosawa Kiyoshi. Thus, the Russian theme is one of the most interesting aspects of his work. At the same time, the author seeks to analyze in details other literary and cinematic origins of Hamaguchi’s directorial career and comes to the conclusion that his work is a complex but harmonious synthesis of Western and Japanese culture with the latter’s pronounced national traditions.